Bilioduodenal anastomosis in rats with extra-hepatic biliary obstruction is followed by lesions ischemia and reperfusion-induced - Ferreira,Márcio Augusto (2008)
PURPOSE: The aim of this study was to investigate alterations compatible with hepatic ischemia-reperfusion after bilioduodenal shunt (BD) in rats with obstructive jaundice (OB) . METHODS: Thirty six animals were divided into 6 experimental groups: CO1 and CO2 - control groups, sham-operated (SO) and evaluated 6 and 24 hours after, respectively; OB1 and OB2, - obstructive jaundice groups, sham-operated 15 days after bile duct ligature and evaluated 6 and 24 hours after SO, respectively; DBD1and DBD2 - obstructive jaundice groups evaluated ,respectively, 6 and 24 hours after BD performed 15 days after bile duct ligature. The parameters evaluated were serum total bilirubin, aminotransferase activity (AST, ALT), TNFalpha, liver mitochondrial functions and parenchymatous injury. RESULTS: Bilirubin decreased while aminotransferase activity increased 6 hours after BD (p<0.01); TNFalpha determination at the 6th hour after BD was higher than the one at the 24th hour (p<0.05); oxygen consumption in states 3 and 4 remained elevated in the BD initial phase , and liver cell damage worsened 24 hours after BD. CONCLUSION: The results demonstrated that surgical biliary decompression in obstructive jaundice is followed by alterations related to hepatic ischemia- reperfusion.